European society of endocrinology curriculum and training recommendation in endocrinology - European Soc Endocrinology ESE (2024)
The European Society of Endocrinology (ESE) and the Union Europ & eacute;enne des M & eacute;decins Sp & eacute;cialistes (U.E.M.S.) Section and Board of Endocrinology have produced a Curriculum and Training Recommendation in Endocrinology to provide updated recommendations concerning the content and structure of postgraduate training. Cornerstones of the Curriculum are the integrity of Endocrinology not to be divided into subspecialties such as diabetology or thyroidology, recommendation of 6 years full-time training comprising 1-3 years (preferably 2-3 years) of General Internal Medicine followed by 3-5 years of specialist training in Endocrinology across 13 core areas. In addition to knowledge and experience in the many fields of Endocrinology, the Curriculum includes specific attitudes, communication skills, training to work in and lead multidisciplinary teams, resource management, quality assurance, human-error management, and critical incidents reporting as well as the commitment to life-long learning expected from a trainee and from an Endocrinologist. The Curriculum also includes requirements for training centres, for assessment of training and for competencies of trainers. The aim of the ESE Curriculum and Training Recommendation in Endocrinology is to harmonise postgraduate training and help provide the best medical care for patients with endocrine diseases across Europe.